The Banality of a Medium: Iran’s “Woman, Life, Freedom” Movement in the Social Media Mirror - Naderi, Sara (Atlantis, 2025)
The tragic death of Zhina (Mahsa) Amini in September 2022 sparked the largest national movement in Iran since 2009. Iranian Women became the symbolic center and main actors of this movement, with the Kurdish slogan “Woman, Life, Freedom” emerging as its defining motto.. This paper presents a theoretical and exploratory reflection on the “Woman, Life, Freedom” (WLF) movement, focusing on how social media, as a medium, shaped its mainstream representations and trajectory. After a brief genealogical analysis of discourses that place women’s veiling at the core of Iranian national politics, the paper examines how the hyperreal nature of modern reality influences social movements. It argues that social media amplifies the visibility of “hyperreal political subjects,” making them dominant actors in the movement. This transformation of political subjectivity imposed the structural limitation of social media not only on representation but also on the “presence” of political actions. Finally, the paper explores how social media facilitates revolutionary and polarized political strategies, enabling the dismantling of dominant hegemonies while simultaneously discouraging radical and progressive political imagination in building counter-hegemonic discourses.